THE EFFECT OF PROJECT BASED LEARNING MODEL ON COGNITIVE SKILL OF 8th GRADE STUDENTS’ ON DYGESTIVE SYSTEM TOPIC - Wahyuni, Ega; Putri, Rahmah Evita (Universe, 2024)
The background of this research is the lack of application of learning models that are appropriate to the learning material in class VIII SMP N 5 Padang, so that the lack of creativity of students when learning results in a decrease in students' cognitive abilities. So it is necessary to apply a learning model that can hone students' cognitive abilities such as the Project Based Learning model. This study aims to determine the effect of applying the Project-Based Learning (PjBL) learning model on the cognitive abilities of Grade VIII students of SMP/MTs in the material on the digestive system in humans. The research method used was quasi-experimental with a non- equivalent post test only control group design. The samples used in this study were class VIII 1 and VIII 3 of 60 students. data collection is done by giving posttest questions. The results of the analysis showed that the average presentation of the cognitive abilities of the experimental class students was 73.6 and the average presentation of the control class was 56.1. Based on the t test obtained Tcount = 3.51 and ttable = 1.67 with a significance level of 0.025. So from the results of these calculations tcount is greater than ttable (tcount 3.51 > 1.67 ttable) so that H0 is rejected and Ha is accepted. So it can be concluded that there is an effect of the application of the Project-Based Learning (PjBL) learning model on the cognitive abilities of Grade VIII students of SMP/MTs on the subject of the digestive system in humans.